2015
DOI: 10.1111/acem.12585
|View full text |Cite
|
Sign up to set email alerts
|

Use of Prestudy Heparin Did Not Influence the Efficacy and Safety of Rivaroxaban in Patients Treated for Symptomatic Venous Thromboem‐bolism in the EINSTEIN DVT and EINSTEIN PE Studies

Abstract: ObjectivesIn the EINSTEIN DVT and EINSTEIN PE studies, the majority of patients received heparins to bridge the period during venous thromboembolism (VTE) diagnosis confirmation and the start of the study. In contrast to vitamin K antagonists (VKAs), rivaroxaban may not require initial heparin treatment.MethodsTo evaluate the effect of prestudy heparin on the efficacy and safety of rivaroxaban relative to enoxaparin/VKA, the 3‐month incidence of recurrent VTE, and the 14‐day incidence of major and nonmajor cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
(38 reference statements)
0
7
0
1
Order By: Relevance
“…there is no need for initial acute-phase treatment with LMWHs, but they do require a dose change between initial and maintenance phases). Notably, in a phase III trial of rivaroxaban, the majority of patients (84 %) received prestudy heparins for a mean duration of 1 day before starting rivaroxaban, although no remarkable differences emerged in patients not receiving this bridge therapy [89]. It is still uncertain whether one approach has a clinical advantage over another.…”
Section: Discussionmentioning
confidence: 99%
“…there is no need for initial acute-phase treatment with LMWHs, but they do require a dose change between initial and maintenance phases). Notably, in a phase III trial of rivaroxaban, the majority of patients (84 %) received prestudy heparins for a mean duration of 1 day before starting rivaroxaban, although no remarkable differences emerged in patients not receiving this bridge therapy [89]. It is still uncertain whether one approach has a clinical advantage over another.…”
Section: Discussionmentioning
confidence: 99%
“…In the RE-COVER (dabigatran) 62 and Hokusai-VTE (edoxaban) 65 studies, LMWH was also administered for at least 5 days. In the EINSTEIN DVT and PE studies, a cohort of 649 patients received rivaroxaban without prior treatment with heparin 70 . A retrospective post-hoc analysis, comparing this cohort to those who did receive heparin (n=3501), concluded that the use of prestudy heparin did not influence the efficacy and safety of rivaroxaban in patients treated for symptomatic VTE as there were no differences in terms of recurrent VTE or major bleeding.…”
Section: Op Treatment Of Pe Using Doacsmentioning
confidence: 99%
“…For this critical question, 3 Class II studies 87-89 and 8 Class III studies [90][91][92][93][94][95][96][97] were identified comparing the efficacy and safety of NOACs with standard therapy in the treatment of acute VTE. All 3 of the Class II studies 87-89 and 3 of the Class III studies 90,91,94 specifically examined outcomes in patients receiving a diagnosis of isolated DVT, whereas the remaining 5 Class III studies 92,93,[95][96][97] examined cohorts that included patients with DVT and PE.…”
Section: Future Researchmentioning
confidence: 99%
“…The number of deaths, acute coronary syndromes, and abnormal liver function test results were also similar between the 2 groups. The effect of prestudy heparin on the efficacy and safety of rivaroxaban relative to standard therapy and the incidence of bleeding compared with that of patients who did not receive prestudy heparin was evaluated in a Class III study by Prandoni et al 93 This retrospective, post hoc analysis of the EINSTEIN-DVT 87 and EINSTEIN-PE 98 studies found that the majority of patients (84%) enrolled in the EINSTEIN-DVT and PE studies received prestudy heparin but with most (70%) receiving prestudy heparin for 1 day or less. There was no difference observed in the incidence of recurrent VTE or bleeding between the groups.…”
Section: Future Researchmentioning
confidence: 99%